The Effect of Non-Steroidal Anti-Inflammatory Drugs on Tendon-to-Bone Healing: A Systematic Review with Subgroup Meta-Analysis - Duchman, Kyle R. (Iowa Orthop J, 2019)
BACKGROUND: There is some concern that non-steroidal anti-inflammatory drugs (NSAIDs) may impair the healing of certain musculoskeletal tissues. However, the effect of NSAIDs on the specialized fibrocartilaginous transition at the tendon-to-bone interface remains largely unknown. Thus, the purpose of the present study is to investigate the effect of NSAIDs on tendon-to-bone healing following acute injury or surgery. METHODS: A systematic review was performed according to the 2009 Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The PubMed (MEDLINE), Embase, Cumulative Index to Nursing and Allied Health (CINAHL), and SportDiscus databases were searched from the time of database inception to May 14, 2018 to identify all clinical and basic science studies investigating the effect of NSAIDs on tendon-to-bone healing. Methodological quality was assessed using the Methodological Index for Non-Randomized Studies (MINORS) and SYstematic Review Center for Laboratory animal Research (SYRCLE) risk of bias assessment tools for clinical and basic science studies, respectively. A qualitative synthesis of the literature was performed with a subgroup meta-analysis of homogeneous basic science studies. RESULTS: A total of 13 studies, including three clinical and 10 basic science studies, were included. The overall methodological quality of the included clinical studies was poor, while assessment of the basic science studies revealed consistent areas at high or unclear risk of bias. Of the included clinical studies, a single study reported a higher rate of rotator cuff repair failure with selective (COX-2) NSAID use compared with non-selective NSAID use, while no clinical failures were noted with NSAID use following distal biceps tendon repair. Basic science studies had heterogeneous outcome reporting. A subgroup analysis of homogeneous animal studies revealed no significant effect of all NSAIDs (Standard Mean Difference [SMD] -1.05, 95% Confidence Interval [CI] -2.39-0.30, p=0.13) or non-selective NSAIDs on load to failure (SMD -0.62, 95% CI -1.26-0.02, p=0.06). CONCLUSIONS: The current literature does not provide sufficient evidence for or against the use of NSAIDs following acute injury or surgical repair of the tendon-bone interface. Level of Evidence: IV